Exploring Lenggong Valley World Heritage Site’s Brand Equity Dimensions - Noor, Shuhaida Md; Kuthoos, Haja Mydin Abdul (EDP Sciences, 2014)
This study explores the brand equity dimensions of a world heritage destination brand, namely the Lenggong Valley World Heritage Site. The study adopted a survey-based brand equity metrics from a previous study that features 27 brand equity dimensions for products. The 27 dimensions were used as the start-off point in exploring the brand equity dimensions for the focal destination brand. The questions were modified to reflect features of heritage destinations. Principal factor analyses were run on data collected from 100 local tourists. The factor analyses yielded 10 factors, namely Trust, Bonding, Service, Acceptability, Value, Heritage, Ambiance, Knowledge, Persistence and Relevance. A new dimension that emerged from the data was value that encompasses both non-financial and financial dimensions.